BERPIKIR KREATIF DAN INOVATIF DALAM MEMBANGUN JIWA ENTREPRENEUR - Jumari (Istithmar: Jurnal Studi Ekonomi Syariah, 2017)
This article examines the creative and innovative thinking in building the entrepreneurial spirit. With the creative and innovative thinking are the human thought process undertaken to develop themselves, especially in building the entrepreneurial spirit. The figure of the entrepreneur as the ideals of human independence in trying to provide support in realizing the nation’s progress. Evidence that the entrepreneur is able to realize the nation’s progress is the existence in the face of obstacles and challenges as well as creative and innovative thinking so that the obstacles and challenges are not an obstacle to success, but rather as an opportunity. Creative and innovative thinking to try to reverse the mindset that tends to be negative into a positive. The assumption that appear in the form of strong beliefs to himself by maximizing the grace to think the Lord gave humans.